G587(P) Omnipod insulin pumps: our institutional experience. (May 2019) - Godman, A; Arthur, A; Tasker, A
Abstract : Background: Insulin pump therapy in children is now a well recognised treatment offering many advantages. It offers more flexibility, less injections and is proven to reduce the risk of severe hypoglycaemia. Insulin pump use in our centre has increased in the last year, since the introduction of the omnipod pump as a choice. Aim: To evaluate the use of omnipod pumps, both quantitatively and qualitatively, compared to other pumps, namely Medtronic. Setting: District General Hospital with 123 children, aged 2–14 years, with Type 1 Diabetes Mellitus Population: All patients with Type 1 diabetes mellitus commenced on insulin pump treatment from 1 st January 2017 to 31 st December 2017. Methods: For the quantitative analysis we did a retrospective audit of practice using data collected from the electronic medical records system (SCI diabetes). For the qualitative stem we distributed satisfaction questionnaires in outpatient clinics. Results: 58% of patients with type 1 diabetes mellitus in our centre are on insulin pumps (n=123). In 2017, 78% of those started on an insulin pump chose omnipod over medtronic pump (n=27). The median age from time of diagnosis to insulin pump start was 31 months in the omnipod group compared with 3.5 months in other pumps. This difference could be attributed to pump choice which was indicated in some of the qualitative questionnaires. 53% of patients on omnipod had reduction in their HbA1c after 3 months (n=19) compared with 83% of those on other pumps (n=6). In the questionnaire, 100% of patients on the omnipod pump stated they would recommend it to others. Those on omnipod pumps rated their quality of life higher than those on Medtronic pumps and it also rated higher for flexibility, ease of use and overall satisfaction. Those on omnipod also rated the importance of type of pump as extremely high. Conclusions: Offering omnipod as a choice of pump has increased insulin pump use in our centre. There was no quantative difference in HbA1c reduction between the omnipod and other insulin pumps. Patient satisfaction questionnaires rated quality of life overall higher for those on omnipod pumps.